2018
DOI: 10.1016/j.bbmt.2018.06.035
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Trial of Extracorporeal Photopheresis for Chronic Graft-versus-Host Disease Reveals Significant Disease Response and No Association with Frequency of Regulatory T Cells

Abstract: Extracorporeal photopheresis (ECP) is an accepted treatment for chronic graft-versus-host disease (cGVHD); however, the mechanism of action is unclear. We conducted a prospective multicenter clinical trial to assess ECP response rates using the 2005 National Institutes of Health (NIH) consensus criteria and to assess the relationship between regulatory T cells (Tregs) and treatment response (NCT01324908). Eighty-three patients with any NIH subtype of cGVHD were enrolled, irrespective of number of prior lines o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 40 publications
0
29
1
3
Order By: Relevance
“…Gandelmann et al reported that 55 % of patients with chronic cutaneous GVHD (89.6 % of the total study population) showed a response to ECP. In the subpopulation of patients with sGVHD (58 %), there was no significant improvement in sclerosis in terms of the body surface area affected [14]. It should be noted, though, that the study duration of only six months was too short for patients with sGVHD; a significant response was therefore not to be expected.…”
Section: Dear Editorsmentioning
confidence: 89%
See 2 more Smart Citations
“…Gandelmann et al reported that 55 % of patients with chronic cutaneous GVHD (89.6 % of the total study population) showed a response to ECP. In the subpopulation of patients with sGVHD (58 %), there was no significant improvement in sclerosis in terms of the body surface area affected [14]. It should be noted, though, that the study duration of only six months was too short for patients with sGVHD; a significant response was therefore not to be expected.…”
Section: Dear Editorsmentioning
confidence: 89%
“…Results of prospective trials of large cohorts have been published [14,15]. In the subpopulation of patients with sGVHD (58 %), there was no significant improvement in sclerosis in terms of the body surface area affected [14]. In the subpopulation of patients with sGVHD (58 %), there was no significant improvement in sclerosis in terms of the body surface area affected [14].…”
Section: Dear Editorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ergebnisse prospektiver Untersuchungen an größeren Patientenkollektiven sind publiziert [14,15]. In der Subpopulation der Patienten mit sGvHD (58 %) ergab sich bezogen auf die betroffene KĂśrperoberfläche keine signifikante Verbesserung der Sklerose [14]. In der Subpopulation der Patienten mit sGvHD (58 %) ergab sich bezogen auf die betroffene KĂśrperoberfläche keine signifikante Verbesserung der Sklerose [14].…”
unclassified
“…Die nationalen europäischen, britischen als auch amerikanischen Leitlinien sprechen sich deutlich fĂźr den Einsatz der ECP bei einer GvHD aus [2,[10][11][12][13]. Ergebnisse prospektiver Untersuchungen an größeren Patientenkollektiven sind publiziert [14,15]. Gandelmann et al konnten zeigen, dass insgesamt bei 55 % aller behandelten Patienten mit einer chronisch kutanen GvHD (89,6 % des Gesamtkollektivs) ein Ansprechen zu verzeichnen war.…”
unclassified